Impact of Human Capital Management Maturity on Employee Performance in PT XYZ - Craven Putra Aditya; Dematria Pringgabayu (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to analyze the effect of Human Capital Management (HCM) maturity dimensions, including leadership practices, employee engagement, knowledge accessibility, workforce optimization, and learning capacity, on employee performance at PT XYZ's Heavy Industry Unit. Research Methodology: A quantitative cross-sectional survey was conducted involving 201 employees selected from a population of 270 through proportionate stratified sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The findings show that all HCM Maturity dimensions positively and significantly affect employee performance. Leadership practices had the strongest influence, followed by learning capacity and knowledge accessibility. The model explains 56.3% of the variance in employee performance. Conclusions: HCM Maturity plays an important role in improving employee performance and organizational effectiveness in the heavy industry sector. Strengthening leadership, learning capacity, and knowledge management can support productivity improvements. Limitations: This study focuses on a single business unit and applies a cross-sectional design, limiting the generalizability of the results. Contributions:  This study provides empirical evidence of  the integrative effect of HCM Maturity dimensions on employee performance in a state-owned heavy industry context, a setting underrepresented in the existing literature, and offers actionable prioritization guidance for human capital practitioners.